2015
DOI: 10.1179/2055075815y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of iron by manganese promoters in uniform bimetallic FeMn Fischer–Tropsch model catalysts prepared from colloidal nanoparticles

Abstract: A systematic study was carried out to investigate the response of monodisperse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…75,76 Recently, monodisperse Fe and FeMn flat model systems were prepared using the hydrothermal decomposition of Fe and Mn oleate complexes, spin-coated on the TEM silica wafers. 46 It was shown that, after reduction, the manganese promotion affects the size and dispersion of Fe oxides and retards their sintering, to an extent. Elemental mapping of the FeMn catalyst surface after three different treatments is shown in Figure 7.…”
Section: ■ Introductionmentioning
confidence: 99%
“…75,76 Recently, monodisperse Fe and FeMn flat model systems were prepared using the hydrothermal decomposition of Fe and Mn oleate complexes, spin-coated on the TEM silica wafers. 46 It was shown that, after reduction, the manganese promotion affects the size and dispersion of Fe oxides and retards their sintering, to an extent. Elemental mapping of the FeMn catalyst surface after three different treatments is shown in Figure 7.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Manganese has been reported to be an electronic promoter that alters the chemisorption species on the catalyst surface and a structural promoter that enhances the dispersion of the active phase during the FTO process [9,42,43]. The necessity for the addition of Mn during the FTO process was reported in our previous work [23][24][25].…”
Section: Effect Of the Catalyst Supportmentioning
confidence: 93%
“…Iron oxide nanoparticles colloid in toluene were prepared as addressed in refs and . The solution was further diluted by toluene to a desired concentration, then the diluent was deposited dropwise on a SiN membrane of a microheater device fabricated using MEMS technology (microelectronic mechanical systems) and dried at room temperature (RT) prior to loading into the ETEM system (FEI Titan ETEM, operated at 300 kV) .…”
Section: Methodsmentioning
confidence: 99%